Long noncoding RNA MAGI1-IT1 promoted invasion and metastasis of epithelial ovarian cancer via the miR-200a/ZEB axis. Issue 12 (18th June 2019) - Gao, Hao; Li, Xiaofeng; Zhan, Guangxi; Zhu, Yong; Yu, Jing; Wang, Jiapo; Li, Li; Wu, Weimin; Liu, Na; Guo, Xiaoqing
ABSTRACT: Epithelial ovarian cancer (EOC) is the most lethal gynecologic malignancy, and its vulnerability to metastasis contributes to the poor outcomes of EOC patients. Long noncoding RNAs (lncRNAs) were verified to play a pivotal role in EOC metastasis. However, the potential role of lncRNA membrane-associated guanylate kinase inverted 1 (MAGI1) intronic transcript (MAGI1-IT1) in EOC is largely unknown. In this study, the function and mechanisms of MAGI1-IT1 in EOC metastasis were explored profoundly. First, MAGI1-IT1 expression was found to be significantly decreased in overexpressing miR-200a EOC cells. Second, MAGI1-IT1 expression was remarkably increased in metastatic EOC tissues, and high MAGI1-IT1 was dramatically associated with EOC FIGO III-IV stage; in addition, MAGI1-IT1 might be related to EOC dissemination via epithelial-mesenchymal transition (EMT). Next, a series of gain- and loss-of-function assays verified that, although MAGI1-IT1 has no significant role in EOC proliferation and subcutaneous xenograft growth, the upregulation of MAGI1-IT1 can remarkably facilitate EOC EMT phenotype, cells migration and invasion ability and intraperitoneal metastasis in nude mice, while downregulation of MAGI1-IT1 led to the opposite effect in vitro . Moreover, MAGI1-IT1 was validated to promote EOC metastasis through upregulation of ZEB1 and ZEB2 by competitively binding miR-200a, and the restrictive effects of MAGI1-IT1 depletion on EOC metastasis could be reversed by inhibition of miR-200a and upregulation of ZEB1 and ZEB2. Collectively, these results suggest that MAGI1-IT1 may work as a ceRNA in promoting EOC metastasis through miR-200a and ZEB1/2 and may be a potential therapeutic target for EOC.